High Levels of Circulating IL-8 and Soluble IL-2R Are Associated With Prolonged Illness in Patients With Severe COVID-19 - Ma, Aiping; Zhang, Liang; Ye, Xiaokai; Chen, Jing; Yu, Jie; Zhuang, Liangjin; Weng, Chaohang; Petersen, Frank; Wang, Zhanxiang; Yu, Xinhua (Frontiers in Immunology, 2021)
Objectives The coordinated immune response of the host is the key of the successful combat of the body against SARS-CoV-2 infection and is decisive for the development and progression of COVID-19. In this study, we aimed to investigate whether the immunological phenotype of patients are associated with duration of illness in patients with severe COVID-19. Method In this single-center study, 69 patients with severe or critical COVID-19 were recruited retrospectively. Immunological parameters including counts of white blood cells, neutrophils, lymphocytes, the neutrophil-to-lymphocyte ratio, and levels of circulating cytokines and cytokine receptors were screened for their association with disease severity, survival and duration of illness of COVID-19. Results Our data confirmed previous results that neutrophil-to-lymphocyte ratio and circulating levels of IL-6 represent prominent biomarker for the prediction of disease severity and survival of COVID-19. However, this study shows for the first time that duration of illness in patients with severe COVID-19 is positively associated with serum levels of IL-8 (P=0.004) and soluble IL-2Rα (P=0.025). Conclusion The significant association of duration of illness with circulating levels of IL-8 and soluble IL-2Rα in patients with severe COVID-19 implicates that neutrophils and T cells are involved in the evolution of COVID-19.